2020
DOI: 10.3390/diagnostics10070501
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chromosome 9 Numerical Imbalances in Oral Squamous Cell Carcinoma: A Pilot Grid-Based Centromere Analysis

Abstract: Oral squamous cell carcinoma (OSCC) is considered an aggressive malignancy, mainly due to its increased propensity to provide local and distant lymph node metastases. Gross chromosome instability (CI; polysomy/aneuploidy/monosomy), combined or not with specific gene alterations, is implicated in the development and progression of solid malignancies, including OSCC. In order to further study the relationship between these genetic alterations and the aggressive biological behavior of OSCCs, we investigated the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…Such findings agreed with Kyrodimos, et al 22 study that showed that cyclin d1 expression was associated to stage and grade of the examined patients (p value=0.001; 0.0014, respectively).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Such findings agreed with Kyrodimos, et al 22 study that showed that cyclin d1 expression was associated to stage and grade of the examined patients (p value=0.001; 0.0014, respectively).…”
Section: Discussionsupporting
confidence: 92%
“…Such findings agreed with Kyrodimos, et al 22 that showed statistical correlation of P53 regarding anatomic location (glottic), (p value =0.44).…”
Section: Discussionsupporting
confidence: 92%
“…Concerning the histo-molecular profile of the previously described malignant neoplasms, recently published studies explored the impact of gross chromosome and specific gene numerical aberrations on their clinicpathological features [24][25][26]. Additionally, epigenetic and micro-molecular factors, including hyper-hypo methylation and microRNAs, seem to be very promising markers for prognosis and targeted therapeutic strategies in subsets of patients suffering from oral malignancies [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%